Phthalimide Analogs Enhance Genotoxicity of Cyclophosphamide and Inhibit Its Associated Hypoxia - Gamal-Eldeen, Amira M.; Agwa, Hussein S.; Zahran, Magdy A.-H.; Raafat, Bassem M.; El-Daly, Sherien M.; Banjer, Hamsa J.; Almehmadi, Mazen M.; Alharthi, Afaf; Hawsawi, Nahed M.; Althobaiti, Fayez; Abo-Zeid, Mona A. M. (Frontiers in Chemistry, 2022)
Cyclophosphamide (CP) is a mutagen that is used in cancer chemotherapy, due to its genotoxicity and as an immunosuppressive agent. Thalidomide (TH) is another cancer chemotherapeutic drug. In this study, the cytogenotoxicity and hypoxia modulatory activities of two phthalimide analogs of TH have been evaluated with/without CP. Both analogs have increased CP-stimulated chromosomal aberrations than those induced by TH, including gaps, breaks/fragments, deletions, multiple aberrations, and tetraploidy. The analogs have elevated the cytotoxic effect of CP by inhibiting the mitotic activity, in which analog 2 showed higher mitosis inhibition. CP has induced binucleated and polynucleated bone marrow cells (BMCs), while micronuclei (MN) are absent. TH and analogs have elevated the CP-stimulated binucleated BMCs, while only analogs have increased the CP-induced polynucleated BMCs and inhibited the mononucleated BMCs. MN-BMCs were shown together with mononucleated, binucleated, and polynucleated cells in the CP group. Both analogs have elevated mononucleated and polynucleated MN-BMCs, whereas in presence of CP, TH and analogs have enhanced mononucleated and binucleated MN-BMCs. The analogs significantly induce DNA fragmentation in a comet assay, where analog 1 is the strongest inducer. The treatment of mice with CP has resulted in a high hypoxia status as indicated by high pimonidazole adducts and high HIF-1α and HIF-2α concentrations in lymphocytes. Analogs/CP-treated mice showed low pimonidazole adducts. Both analogs have inhibited HIF-1α concentration but not HIF-2α. Taken together, the study findings suggest that both analogs have a higher potential to induce CP-genotoxicity than TH and that both analogs inhibit CP-hypoxia via the HIF-1α-dependent mechanism, in which analog 1 is a more potent anti-hypoxic agent than analog 2. Analog 1 is suggested as an adjacent CP-complementary agent to induce CP-genotoxicity and to inhibit CP-associated hypoxia.